Ten-Year Trend in Women's Reasons for Abstaining or Limiting Drinking: The 2000 and 2010 United States National Alcohol Surveys - Karriker-Jaffe, Katherine J. (J Womens Health (Larchmt), 2018)
Background: Data on individual and cultural factors contributing to drinking can inform screening and brief intervention in clinical practice. Our aims were to examine 10-year trends in women's reasons for abstaining/limiting drinking and to document changes in associations with drinking status for population subgroups defined by race/ethnicity and age. Materials and Methods: Using repeated cross-sectional data from White, Black and Hispanic women in the 2000 and 2010 United States National Alcohol Surveys (combined N = 5501), population-weighted multiple linear and multinomial logistic regression models assessed changes in three reasons for abstaining or limiting drinking (health concerns, religious prohibition, and upsetting family or friends) and drinking status (past-year abstainer, low-risk drinker, or at-risk drinker), and their associations over time. Results: Adjusting for key demographics, reasons for limiting alcohol consumption declined in importance over time, with reductions in both health concerns and religious prohibition particularly noteworthy for older women of all three racial/ethnic backgrounds. Despite these reductions in importance, both health concerns and religious prohibition were most consistently associated with increased abstinence relative to low-risk drinking; these reasons were not strongly associated with at-risk drinking, however. Conclusions: It is essential for healthcare providers and others to disseminate accurate information about the risks of drinking to counter cultural shifts that suggest greater acceptance of moderate-to-heavy drinking by women aged 40 and older.